Simple Cloud Point Extraction-Spectrophotometric for the Determination for Lead (II) Using-3-Anilino-1-Phenylimino-Thiourea - Ali Ahssan Hamz Najm, Ahmed S. Abbas, (Pakistan Journal of Medical & Health Sciences, 2022)
After complexing with 3-anilino-1-phenylimino-thiourea (R.), the cloud-point extraction (CPE) process was used to enrich lead (II), which was then analyzed using uv–visible spectrometry using Triton X-114 as a suitable non-ionic surfactant. pH, concentration for (R) and volume Triton X-114(0.6ml), equilibration temperature 50C and duration, and lastly centrifugation (rate and time)4,000 rpm,20 min have all been enhanced as experimental variables that impact the CPE process. Pre-concentration of sample in a 5 mL solution contains 2.5 percent (v/v) starting with the influence of pH at (4.2). The detection (LOD) of (0.018) μg.mL-1 of lead (+2) and the limit of quantification (LOQ) of (0.08) μg.mL-1 were achieved using Triton X-114 with 1×10-3 mol.L-1 of (R.). A linear calibration curve with a precision of relative standard deviation (R.S.D, n =7,0.3 μg. mL-1 Pb (II)) were obtained within the range (0.06 -3.0) μg.mL-1. Keywords: Pb+2; Triton( X—114) ,Clo’ud point extra’ction(C.P.E); 3-anilino-1-phenylimino-thiourea;